Defect-implantation for the all-electrical detection of non-collinear spin-textures - Imara Lima Fernandes (Nature Portfolio, 2020)
Precise detection of magnetic skyrmions is a key prerequisite to exploit them in future magnetic storage technologies. The authors, using first principles studies, propose two novel spin-mixing magnetoresistance effects enabled by defects, which allow for a highly efficient all-electrical detection of spin-swirling textures.